Associations Between Peer Victimization and Suicidal Ideation and Suicide Attempt During Adolescence: Results From a Prospective Population-Based Birth Cohort - Geoffroy, Marie-Claude; Boivin, Michel; Arseneault, Louise; Turecki, Gustavo; Vitaro, Frank; Brendgen, Mara; Renaud, Johanne; Séguin, Jean R; Tremblay, Richard E; Côté, Sylvana M (Journal of the American Academy of Child and Adolescent Psychiatry, 2016)
To test whether adolescents who are victimized by peers are at heightened risk for suicidal ideation and suicide attempt, using both cross-sectional and prospective investigations. Participants are from the Quebec Longitudinal Study of Child Development, a general population sample of children born in Quebec in 1997 through 1998 and followed up until 15 years of age. Information about victimization and serious suicidal ideation and suicide attempt in the past year was obtained at ages 13 and 15 years from self-reports (N = 1,168). Victims reported concurrently higher rates of suicidal ideation at age 13 years (11.6-14.7%) and suicide attempt at age 15 years (5.4-6.8%) compared to those who had not been victimized (2.7-4.1% for suicidal ideation and 1.6-1.9% for suicide attempt). Being victimized by peers at 13 years predicted suicidal ideation (odds ratio [OR] = 2.27; 95% CI = 1.25-4.12) and suicide attempt (OR = 3.05, 95% CI = 1.36-6.82) 2 years later, even after adjusting for baseline suicidality and mental health problems and a series of confounders (socioeconomic status, intelligence, family's functioning and structure, hostile-reactive parenting, maternal lifetime suicidal ideation/suicide attempt). Those who were victimized at both 13 and 15 years had the highest risk of suicidal ideation (OR = 5.41, 95% CI = 2.53-11.53) and suicide attempt (OR = 5.85, 95% CI = 2.12-16.18) at 15 years. Victimization is associated with an increased risk of suicidal ideation and suicide attempt over and above concurrent suicidality and prior mental health problems. The longer the history of victimization, the greater the risk.